2023
DOI: 10.3390/children10091479
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Speckle-Tracking Echocardiography with Traditional Biomarkers in Predicting Cardiotoxicity among Pediatric Hemato-Oncology Patients: A Comprehensive Evaluation of Anthracycline Dosages and Treatment Protocols

Andrada Mara Ardelean,
Ioana Cristina Olariu,
Raluca Isac
et al.

Abstract: Speckle tracking-echocardiography (STE) is a novel non-invasive imaging tool capable of quantifying myocardial deformation, and thus holds promise in detecting early subclinical myocardial injury. This study aimed to evaluate the correlation of STE with traditional biomarkers in predicting anthracycline-induced cardiotoxicity in the context of varying dosages and treatment protocols in pediatric hemato-oncology patients. We conducted a retrospective study involving pediatric hemato-oncology patients undergoing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In addition, some indices, such as TAPSE (tricuspid annular plane systolic excursion), are reported to be more sensitive for asymptomatic CTRCD detection [51]. However, when searching for a correlation of STE (GLS) with traditional biomarkers in predicting cardiotoxicity among pediatric patients, the ROC analysis did not find GLS to be a significant independent predictor of cardiotoxicity (p > 0.05) [52]. Nevertheless, unlike STE, three-dimensional TTE is relatively cost-effective and available and, as such, remains in the range of tools for CTRCD diagnosing.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some indices, such as TAPSE (tricuspid annular plane systolic excursion), are reported to be more sensitive for asymptomatic CTRCD detection [51]. However, when searching for a correlation of STE (GLS) with traditional biomarkers in predicting cardiotoxicity among pediatric patients, the ROC analysis did not find GLS to be a significant independent predictor of cardiotoxicity (p > 0.05) [52]. Nevertheless, unlike STE, three-dimensional TTE is relatively cost-effective and available and, as such, remains in the range of tools for CTRCD diagnosing.…”
Section: Discussionmentioning
confidence: 99%
“…[26] Our values of LVEF were in agreement with those in the study conducted by Ardelean A. et al where they showed mean values of LVEF of of 62.1 ± 5.5% for the patients receiving Doxorubicin treatment and 64.7 ± 5.9% for those treated with Epirubicin. [27] The role of sex in the development of anthracycline cardiotoxicity in the pediatric population is yet to be studied. [28] There are some studies for oncologic pediatric population that have reported that female are at risk for developing cardiac atrophy, as measured by a decrease in left ventricular mass, and subsequent HF.…”
Section: Discussionmentioning
confidence: 99%